Patterns of precarious employment in a female-dominated sector in five affluent countries: The case of paid domestic labor sector in five welfare states - Merita Jokela (Luxembourg Income Study (LIS), 2018)
This is the first quantitative comparative study that examines the relationship between paid domestic labor and precarious employment on the micro-level. Using the Luxembourg Income Study 2013/2014, it shows that across welfare regimes, domestic workers have a higher probability of working in precarious employment settings compared to other industries. Furthermore, the overlaps of two or more precarious employment settings are significantly more common in domestic work than among other industries in all countries examined. This is an important finding as it proves the high insecurity of the formal domestic labor industry even in countries with specific regulations regarding domestic work.
Keywords: 330; care work; comparative research; female employment; paid domestic work; precarious employment